Risk Factors for Delayed Hyperthyrotropinemia in Late Preterm Infants - Mun Hui Jeong; Narae Lee; Mi Hye Bae; Young Mi Han; Kyung Hee Park; Shin Yun Byun (Korean Society of Neonatology, 2019)
Purpose This study aimed to investigate the prevalence of delayed thyroid dysfunction based on iodine disinfectant use and to analyze associated risk factors. Methods A retrospective study was conducted on late preterm infants admitted to the neonatal intensive care unit between January 2010 and June 2018, who underwent neonatal thyroid screening (NTS) and ≥2 thyroid function tests (TFTs). NTS was performed 3 days after birth, with at least two TFTs 1 week and 2 to 4 weeks after birth. To distinguish between normal and dysfunctional thyroid levels, we reviewed TFT results at 2 to 4 weeks and examined possible risk factors for the development of thyroid dysfunction. Results Of 295 late preterm infants, 262 were enrolled with a mean gestational age and birth weight of 34.8±0.7 weeks and 2,170±454 g, respectively. A total of 7.6% developed hyperthyrotropinemia at the age of 24.3±14.6 days (range, 12 to 69). The incidence of hyperthyrotropinemia during iodine use was approximately 12.6%, while that during discontinuation was 2.4% (P=0.002). Multivariate analysis revealed that small for gestational age (SGA), iodine disinfectant use, and abnormal NTS results were significant risk factors for delayed hyperthyrotropinemia (adjusted odds ratio [AOR]: 4.27, P=0.008; AOR: 8.24, P=0.003; and AOR: 7.80, P=0.002, respectively). Conclusion Delayed hyperthyrotropinemia was prevalent in late preterm infants exposed to topical iodine and those identified as being SGA. Secondary TFTs should be considered 2 to 4 weeks after birth for this population at risk.